Stature Estimation Using Hand and Foot Metrics among the Meena Tribal Population of the North-western Indian Region - Suraj Kataria; Shivani Dechalwal; Rutwik Shedge; Naorem Kiranmala Devi; Mohinder P. Sachdeva; Sonal Jain (Wolters Kluwer Medknow Publications, 2024)
Background: Studies on stature estimation models for North West Indian populations are limited. The present study attempts to develop stature estimation models for the Indian population using hand and foot dimensions. Materials and Methods: Hand and foot measurements of 280 individuals (140 males and 140 females) were recorded for the estimation of stature in the present study. The stature and nine hand and foot anthropometric measurements were obtained using standard methods and relevant landmarks. For bilateral and sex differences, independent and paired t-tests were used to statistically analyze the data. Results: The findings showed statistically significant sex differences (P < 0.05) in stature, foot, and hand measurements. However, there were no significant bilateral differences. The Pearson correlation coefficient assessed the association between stature and hand/foot measurements. All the studied parameters in both sexes demonstrated a statistically significant (P < 0.001) and strong positive correlation with stature. Males and females had the strongest correlation coefficients for right-foot length (r = 0.70) and right-hand length (r = 0.64), respectively. Each sex's regression equations were calculated separately. Stature predictions were accurate to within 4.02-6.64 cm. Conclusion: Stature estimated from hand and foot measurements can help in personal identification by creating an individual's biological profile. Morphological differences in feet and hands demonstrate the significance of developing ethnic group-specific models to determine stature. According to the study's findings, the stature of a person belonging to the Indian subcontinent can be estimated using hands and feet for anthropological and forensic purposes.